Analisis Penentuan Harga Jual berdasarkan Metode Variable Costing dan Job Order Costing pada IKM Sabda Batik Ecoprint - Wiwik Hestiningsih (JFAS : Journal of Finance and Accounting Studies, 2022)
Company would expect the maximum profit for his efforts. The achievement of profit maximally strongly influenced by the calculation of the cost of production, the determination of the selling price, and sales volume of a product appropriately. This study aims to determine the calculation of the cost of production in IKM Sabda Batik Ecoprint Jombang in determining the selling price and the next will be compared with the calculations of the researchers using the method of variable costing and job order costing. Types of research method used is qualitative research with descriptive approach. The information in the qualitative method is obtained by means of observation, interview, and documentation. The results showed that the calculation of cost of production in IKM Sabda Batik Ecoprint Jombang using the method of full costing. The calculation is to obtain a higher yield than the calculation of the cost of production based on the method of variable costing and job order costing. These results are aligned with the determination of the product selling price fabric ecoprint is the selling price per unit based on the method of full costing obtain a result that is higher than the selling price per unit based on the method of variable costing and job order costing. Key words: Selling price; variable costing; Job Order Costing